2018
DOI: 10.3390/nu10060764
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Cholesterol on the Pathophysiology of Infectious and Autoimmune Disease

Abstract: Cellular cholesterol metabolism, lipid raft formation, and lipoprotein interactions contribute to the regulation of immune-mediated inflammation and response to pathogens. Lipid pathways have been implicated in the pathogenesis of bacterial and viral infections, whereas altered lipid metabolism may contribute to immune dysfunction in autoimmune diseases, such as systemic lupus erythematosus, multiple sclerosis, and rheumatoid arthritis. Interestingly, dietary cholesterol may exert protective or detrimental eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 191 publications
(292 reference statements)
1
48
0
Order By: Relevance
“…Recently, increasing studies have found that dyslipidemia in patients with SLE plays a key role in the development of atherosclerosis [7][8][9][10]18]. It seems that atherosclerosis frequently appears during the process of SLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, increasing studies have found that dyslipidemia in patients with SLE plays a key role in the development of atherosclerosis [7][8][9][10]18]. It seems that atherosclerosis frequently appears during the process of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studys showed that the patients with SLE had twofold higher risk of cardiovascular disease as compared to control, and SLE patients with lupus nephritis display significantly increased risk of myocardial infarction and cardiovascular disease mortality than SLE patients without lupus nephritis [5,6]. Additionally, SLE disease-related parameters could be taken into consideration when calculating cardiovascular disease risks, and most of the patients with SLE were diagnosed with dyslipidemia, suggesting that dyslipidemia could be a critical factor in the progression of cardiovascular disease in SLE [7][8][9][10]. The patients with SLE exhibited increased total cholesterol (TC), triglycerides (TG) and very lowdensity lipoprotein-cholesterol (VLDL-C), and decreased high-density lipoprotein-cholesterol (HDL-C) and apolipoprotein A (Apo A) compared with control [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent systematic review (62) and meta-analysis (63) showed that only a consumption of high cholesterol can increase serum cholesterol by up to 5 %. Some studies have found it difficult to verify this result because of confounding factors, such as body mass, which has an influence on cholesterol metabolism (56,63) . Obese people appear to absorb more cholesterol compared with lean individuals (64) .…”
Section: -Month Interdisciplinary Interventionmentioning
confidence: 98%
“…Thus, we believe that serum adipokine concentrations in the present study were not problematic, as these were below the values obtained in other studies with obese adolescents (27,53) . In addition, the fact that adipokine concentrations remain similar after interdisciplinary intervention suggests that other factors, besides fat percentage and BMI (53,55,56) , may be involved in the expression of adiponectin and leptin, such as sexual maturation (57) .…”
Section: -Month Interdisciplinary Interventionmentioning
confidence: 99%
“…Several studies suggest also an autoimmune response [43,44] in atherosclerosis with a switch in regulatory T cells from an initial protective phenotype (FoxP3+) into a pathogenic one (RORγt, T-bet, Bcl-6) [45].…”
Section: The Role Of Atherosclerosismentioning
confidence: 99%